2023
DOI: 10.3390/diagnostics13030432
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Involvement in Tuberculosis: From Pathophysiology to Diagnosis and Complications—A Narrative Review

Abstract: Although primarily a lung disease, extra-pulmonary tuberculosis (TB) can affect any organ or system. Of these, cardiovascular complications associated with disease or drug toxicity significantly worsen the prognosis. Approximately 60% of patients with TB have a cardiovascular disease, the most common associated pathological entities being pericarditis, myocarditis, and coronary artery disease. We searched the electronic databases PubMed, MEDLINE, and EMBASE for studies that evaluated the impact of TB on the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 165 publications
0
20
0
Order By: Relevance
“…al., (2023) reported an 8% [aHR: 1.08 (0.99-1.18)] higher risk of incident ischemic heart disease or stroke with LTBI compared to no TB (25). Their study included 49,197 immigrants to Canada (1985-2019) with total follow-up of 901,734 person-years and a median time of 19 years from cohort entry to censoring. We also found reduced cardiovascular-specific survival with LTBI in a mixed US cohort of immigrants and born citizens which was, however, not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al., (2023) reported an 8% [aHR: 1.08 (0.99-1.18)] higher risk of incident ischemic heart disease or stroke with LTBI compared to no TB (25). Their study included 49,197 immigrants to Canada (1985-2019) with total follow-up of 901,734 person-years and a median time of 19 years from cohort entry to censoring. We also found reduced cardiovascular-specific survival with LTBI in a mixed US cohort of immigrants and born citizens which was, however, not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Overlap with traditional risk factors may accentuate this risk as we observed with comorbid LBTI and diabetes mellitus in our results. From a mechanistic standpoint, an amplified and dysregulated inflammatory response to M.tb antigens drives insulin resistance, hypercoagulability, endothelial dysfunction and microvascular dysfunction, among others (18), (19), (49), (50), (51). Intermediate states like hypertension (52) and diabetes/hyperglycemia (53), (54), whose incidence is shown to be increased with LTBI, may be the proximate drivers of morbidity and mortality independent of progression to active TB.…”
Section: Discussionmentioning
confidence: 99%
“…HF in SSA can arise from infectious diseases such as mycobacterium tuberculosis or HIV, which can lead to rheumatic heart disease, cardiomyopathies, and pericarditis. 82,83 Notably, the VALVAFRIC study (a registry of patients with rheumatic heart disease [RHD] hospitalized in African cardiology departments from 2004 to 2008) found that among patients with severe rheumatic valvular lesions, 57.9% were women or girls in SSA, totaling 803 of 1385 cases. 82 Moreover, the study revealed a higher likelihood of the progression of rheumatic heart disease in regions of SSA characterized by higher levels of poverty.…”
Section: Underdiagnosing Hypertension and Hdp In Ssamentioning
confidence: 99%
“…5, 6 Lately, research attention has been drawn to likely long-term detrimental cardiovascular effects of infection with Mycobacterium tuberculosis (M.tb). 7, 8 A recent (2020) meta-analysis summarizing extant studies, estimated the risk of incident CVD with prior tuberculosis (TB) to be 1.5 times [risk ratio 1.51 (95%CI: 1.16-1.97)] higher than without a history of TB. 9 Of note is that the included studies were largely drawn from high-income countries (HICs).…”
Section: Introductionmentioning
confidence: 99%
“…18, 19 Their multimorbidity 20, 21 is very common, raising the possibility that immune activation and systemic inflammation associated with co-occuring HIV/TB likely negatively impacts the cardiovascular system. 7, 8 APHIV experiencing TB may therefore be predisposed to premature cardiac morbidity and mortality as they enter adulthood.…”
Section: Introductionmentioning
confidence: 99%